Effect of unground palm oil fuel ash as partial sand replacement on compressive strength of oil palm shell lightweight concrete - Saffuan, Wan Ahmad; Khairunisa, Muthusamy; M. H., Hashim; A. M., Albshir Budiea; Nur Farhayu, Ariffin (2019)
Concern towards degradation of environment due to increasing use of natural sand in construction industry and dumping of solid wastes from palm oil industry namely palm oil fuel ash and oil palm shell has lead towards the development of environmental friendly concrete. The present study investigates the effect of unground palm oil fuel ash as partial sand replacement towards workability and compressive strength of oil palm shell lightweight aggregate concrete. Two types of mixes were used. Control specimen was prepared using 100% natural sand. Another type of mix were prepared by integrating 5%, 10% and 15% unground palm oil fuel ash by weight of sand. The concrete mixes workability were investigated by conducting slump test in accordance to standard. All specimens were made in form of cubes (150mm x150mm) and water cured up to 28 days. The compressive strength test was carried out in accordance to BS EN12390: 3 at 1, 4, 7 and 28 days. The finding shows that integration of 10% unground palm oil fuel ash contributes to the enhancement of oil palm shell lightweight aggregate concrete properties. Success in using unground POFA as partial sand replacement in concrete production would reduce quantity of ash disposed as waste and save the consumption of natural river sand.